PENDIDIKAN AGAMA ISLAM DI THAILAND - Abdul Wahab Syakhrani (CV. ADIBA AISHA AMIRA, 2022)
Islam in Thailand is a minority group that has emerged since the thirteenth century AD in southern Thailand, especially the Pattani and Songkhla areas. In its journey, Islam grew very difficult in Thailand, because it was always under pressure from the Buddhist-majority government. Not much different, Islamic education was very difficult to develop, at first Islamic education was informal, just a hut, then developed into a madrasa. However, in the late 1970s there were attacks after attacks from the military against these institutions, and even ustadz were also included in the targets of the attacks. All of this was carried out by the Thai government under the pretext of eradicating the rebellion by the Pattani fighters.